2016
DOI: 10.1128/aac.00007-16
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Transfer of Raltegravir in an Ex Vivo Human Cotyledon Perfusion Model

Abstract: i Placental transfer of the HIV integrase inhibitor raltegravir (RLT) was investigated in term human cotyledons in the maternalto-fetal (n ‫؍‬ 3) and fetal-to-maternal (n ‫؍‬ 6) directions. In the maternal-to-fetal direction, the mean ؎ standard deviation (SD) fetal transfer rate (FTR) was 9.1% ؎ 1.4%, and the mean ؎ SD clearance index (IC), i.e., RLT FTR/antipyrine FTR, was 0.28 ؎ 0.05. In the fetal-to-maternal direction, the mean ؎ SD CI was 0.31 ؎ 0.09. Placental transfer of RLT was high in both directions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Other publications [122][123][124] computed, for a specific period of time (generally up to 90 min), the fetal transfer rate (FTR, ratio of venous fetal concentration of a substance over maternal concentration) and a clearance index (CLI) as the ratio of the FTR of a substance over the FTR of antipyrine (the fetal perfusion rate is not included in CLI computation).…”
Section: Ex Vivo Placental Perfusion Systemsmentioning
confidence: 99%
“…Other publications [122][123][124] computed, for a specific period of time (generally up to 90 min), the fetal transfer rate (FTR, ratio of venous fetal concentration of a substance over maternal concentration) and a clearance index (CLI) as the ratio of the FTR of a substance over the FTR of antipyrine (the fetal perfusion rate is not included in CLI computation).…”
Section: Ex Vivo Placental Perfusion Systemsmentioning
confidence: 99%
“…The major limitation is the small number of INSTI-exposed pregnancies, in accordance with French national guidelines that favor PI-based therapy for women wishing to become pregnant, thus limiting the power of our analyses. This highlights the importance on maintaining an active research on the possible side effects of any ART given during pregnancy and especially those that have a high placental transfer ratio such as INSTIs [23,24]. Another limitation is that we cannot exclude possible confounding factors that may have not been taken into account, such as viral load and CD4 count at conception, or preexisting conditions and concurrent drugs potentially associated to birth defects as these were not available in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The placental transfer of dolutegravir seems to be higher as compared with the other integrase inhibitors, raltegravir and elvitegravir. For raltegravir, Vinot et al [33] found an FTR in the maternal-to-fetal direction of 9.1% ± 1.4% and a CLI of 0.28 ± 0.05%. For elvitegravir, we have reported in the same closed-circuit model, after 3h of perfusion an FTR of 20% ± 10% [20].…”
Section: Discussionmentioning
confidence: 99%